2017
DOI: 10.1016/j.molcel.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the DNA Damage Response by DNA-PKcs Inhibitory Phosphorylation of ATM

Abstract: SUMMARY Ataxia-Telangiectasia Mutated (ATM) regulates the DNA damage response as well as DNA double-strand break repair through homologous recombination. Here we show that ATM is hyperactive when the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) is chemically inhibited or when the DNA-PKcs gene is deleted in human cells. Pre-incubation of ATM protein with active DNA-PKcs also significantly reduces ATM activity in vitro. We characterize several phosphorylation sites in ATM that are targets of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 44 publications
6
99
0
Order By: Relevance
“…Therefore, indirect effect may not amplify p53 pulses. During the review, Zhou et al identified that DNA-PK phosphorylates ATM at multiple sites and inhibits ATM activity [23]. Our model inference is consistent with Zhou et al’s study.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, indirect effect may not amplify p53 pulses. During the review, Zhou et al identified that DNA-PK phosphorylates ATM at multiple sites and inhibits ATM activity [23]. Our model inference is consistent with Zhou et al’s study.…”
Section: Discussionsupporting
confidence: 90%
“…Since the lack of ATM phosphorylation observed in siING3 cells is not observed in siTIP60 cells, our results suggest that ING3-dependent phosphorylation of ATM is independent on TIP60. One hypothesis would be that ING3 has an inhibitory effect on DNA-PKcs activity which itself negatively regulates ATM phosphorylation 48 . Or, the ATM-linked proliferation inhibition observed in siING3 cells could also be due to the activation of the tumor suppressor ARF, as it has been previously described 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation of Ku70/80 following phosphorylation allows resection to begin, increasing the rate of HR in S phase. DNA-PKcs also regulates HR by modulating the activity of the ATM kinase in response to DNA damage (27). ATM is a master regulator of DNA damage responses, with hundreds of known substrates.…”
Section: Regulation Of Nhejmentioning
confidence: 99%